PENGARUH PERUBAHAN PENGUMUMAN DIVIDEN TERHADAP HARGA SAHAM - Widsatrya, I Wayan Krisna; Subroto, Bambang (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
The purpose of this research is to examine the effect of dividend change announcement, dividend increase, and dividend decrease on stock prices used by the company. By using purposive sampling technique, 55 companies that announced dividend increases and 46 companies that announced dividend decrease on companies listed in Indonesia Stock Exchange during 2010-2014. The data analysis technique uses a one-sample t test and multiple regression analysis. The results show that there are positive abnormal return during the dividend increase announcement and a negative abnormal return during the dividend decrease announcement. In the dividend change announcement, it shows a positive relationship with stock prices. It means that greater change in dividends paid results in higher stock prices. In the dividend increase announcement, there is a positive relationship with stock prices which results in higher stock price. In the case of dividend decrease announcement, it shows no correlation with the stock price. Keywords: Dividend Change, Dividend Increase, Dividend Decrease, Abnormal Return, Stock Price.